Being a teenager and cancer patient: What do adolescents and young adults with cancer find valuable and challenging with their friends and cancer peers?. Issue 2 (3rd March 2020) - Kaluarachchi, Tharushi; McDonald, Fiona; Patterson, Pandora; Newton-John, Toby R. O.
Abstract: Purpose: This study examined Adolescent and Young Adult (AYA) cancer patients' experiences with friends and cancer friends (peers) throughout their cancer journey. Research approach: Qualitative, thematic analysis. Participants: Twelve AYA diagnosed with cancer, treated within the past five years. Methodological approach: Individual semi-structured interviews, focusing on friend and peer experiences pre-/post-diagnosis, during and after treatment. Findings: Overarching themes of 'valued' vs. 'challenging' aspects with friends and peers. Interpretation: Friend and peer relationships were both valuable, but in different ways. Friends provided general support and helped AYA feel like a normal teenager, while peers provided targeted support and helped AYA feel like a normal teenager with cancer. Peers had an intimate understanding of cancer, whereas poor understanding by friends led to further challenges such as avoidance and being dismissive. Peer relations were notably challenged by a premature confrontation with mortality. Friendships evolved and changed throughout the cancer journey.